Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/min6030083
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Chalcopyrite Dissolution at Controlled Redox Potential of 750 mV in Sulfuric Acid Solution

Abstract: Abstract:To better understand chalcopyrite leach mechanisms and kinetics, for improved Cu extraction during hydrometallurgical processing, chalcopyrite leaching has been conducted at solution redox potential 750 mV, 35-75˝C, and pH 1.0 with and without aqueous iron addition, and pH 1.5 and 2.0 without aqueous iron addition. The activation energy (E a ) values derived indicate chalcopyrite dissolution is initially surface chemical reaction controlled, which is associated with the activities of Fe 3+ and H + wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 77 publications
(134 reference statements)
2
14
0
1
Order By: Relevance
“…Watling (2013b) summarized current knowledge in respect of the hydrometallurgical systems of acidic sulfate, sulfate-chloride and sulfate-nitrate, and proposed that atmospheric pressure processes required catalysts, fine grinding or temperature. Li et al (2016) studied the kinetics and mechanisms of chalcopyrite dissolution at controlled redox potential of 750 mV in sulfuric acid solution and found that the addition of aqueous iron played an important role in accelerating Cu leaching rates, especially at lower temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Watling (2013b) summarized current knowledge in respect of the hydrometallurgical systems of acidic sulfate, sulfate-chloride and sulfate-nitrate, and proposed that atmospheric pressure processes required catalysts, fine grinding or temperature. Li et al (2016) studied the kinetics and mechanisms of chalcopyrite dissolution at controlled redox potential of 750 mV in sulfuric acid solution and found that the addition of aqueous iron played an important role in accelerating Cu leaching rates, especially at lower temperature.…”
Section: Introductionmentioning
confidence: 99%
“…These concentrations have been calculated using ICP-OES results, Eh of leachates (both given in Table S2, Supplementary Materials), and the Nernst equation (Equation (3); [25,26]) and are shown in Figure 5. The reaction rate between pyrite and ferric iron was observed by Moses et al [27] to be one to two orders of magnitude greater than between pyrite and dissolved O2 in the pH range of 2-9.…”
Section: Leachate Chemistrymentioning
confidence: 99%
“…Sulfidni minerali imaju stabilnu kristalnu rešetku, pa prilikom njihovog luženja rastvor mora sadržati oksidaciono sredstvo za oksidaciju sulfidnog sumpora. Feri, kupri, nitratni i nitritni joni, kiseonik, bakterije i drugi oksidansi koriste se kao sredstva za luženje sulfidnih minerala u sulfatnim i hloridnim rastvorima pri standardnom i povišenom pritisku [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
unclassified